Pengaruh Metode Match and Share Group Terhadap Kemampuan Menulis Teks Eksposisi - Ridha Wahdatul Fuadah; Edi Puryanto (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to determine the effect of the Match and Share Group (MSG) learning method on the exposition writing skills of tenth-grade students at SMK Farmasi Mandala Tiara Bangsa. It employed a descriptive quantitative approach using a one-group pretest-posttest design. Data were obtained through writing tests given before and after treatment in the experimental class. The treatment was conducted through direct instruction using the MSG method. The instruments and scoring rubrics were validated before use. Results showed a notable increase in student scores, with the average rising from 53 (pretest) to 75.86 (posttest). A normality test confirmed that data were normally distributed: Lo = 0.179 < Ltable = 0.249 (pretest) and Lo = 0.186 < Ltable = 0.249 (posttest) at α = 0.05. Homogeneity test results indicated equal variance (Fcount = 1.352 < Ftable = 4.256). Hypothesis testing showed tcount = 8.032 > ttable = 2.262, meaning H0 was rejected and H1 accepted. These findings suggest that the Match and Share Group method has a significant positive effect on students’ exposition writing skills. Keywords: Match and Share Group; Writing Skills; Exposition Text; Quantitative Research; Vocational High School